(untitled) (The Conference Hub, 2025)
This paper presents a comparative analysis between traditional methods and high-precision GNSS (Global Navigation Satellite System) technologies in the process of tree inventory and registration. The study examines the advantages and limitations of both approaches in managing urban ecological infrastructure, accounting for urban greenery, and determining tree locations. Using Tashkent city as a case study, special attention is given to the accuracy, efficiency, and reliability of GNSS-based measurements. The findings demonstrate that GNSS technologies enable centimeter-level accuracy in determining tree coordinates, provide automatic data integration into digital maps, and facilitate effective environmental monitoring. The paper also highlights the practical benefits and recommendations for transitioning from conventional survey techniques to GNSS-based digital inventory systems.